Spleen Size and Function in Sherpa Living High, Sherpa Living Low and Nepalese Lowlanders - Holmström, Pontus; Mulder, Eric; Starfelt, Victor; Lodin-Sundström, Angelica; Schagatay, Erika (Frontiers in Physiology, 2020)
High-altitude (HA) natives have evolved some beneficial responses leading to superior work capacity at HA compared to native lowlanders. Our aim was to study two responses potentially protective against hypoxia: the spleen contraction elevating hemoglobin concentration (Hb) and the cardiovascular diving response in Sherpa highlanders, compared to lowlanders. Male participants were recruited from three groups: (1) 21 Sherpa living at HA (SH); (2) seven Sherpa living at low altitude (SL); and (3) ten native Nepalese lowlanders (NL). They performed three apneas spaced by a two-min rest at low altitude (1370 m). Their peripheral oxygen saturation (SpO2), heart rate (HR), and spleen volume were measured across the apnea protocol. Spleen volume at rest was 198 ± 56 mL in SH and 159 ± 35 mL in SL (p = 0.047). The spleen was larger in Sherpa groups compared to the 129 ± 22 mL in NL (p < 0.001 compared to SH; p = 0.046 compared to SL). Spleen contraction occurred in all groups during apnea, but it was greater in Sherpa groups compared to NL (p < 0.001). HR was lower in Sherpa groups compared to NL both during rest (SL: p < 0.001; SH: p = 0.003) and during maximal apneas (SL: p < 0.001; SH: p = 0.06). The apnea-induced HR reduction was 8 ± 8% in SH, 10 ± 4% in SL (NS), and 18 ± 6% in NL (SH: p = 0.005; SL: p = 0.021 compared to NL). Resting SpO2 was similar in all groups. The progressively decreasing baseline spleen size across SH, SL, and NL suggests a role of the spleen at HA and further that both genetic predisposition and environmental exposure determine human spleen size. The similar HR responses of SH and SL suggest that a genetic component is involved in determining the cardiovascular diving response.